The (heterogenous) economic effects of private equity buyouts - Steven J. Davis; John C. Haltiwanger; Kyle Handley; Joshua Lerner; Ben Lipsius; Javier Miranda (Halle Institute for Economic Research (IWH), 2022)
The effects of private equity buyouts on employment, productivity, and job reallocation vary tremendously with macroeconomic and credit conditions, across private equity groups, and by type of buyout. We reach this conclusion by examining the most extensive database of U.S. buyouts ever compiled, encompassing thousands of buyout targets from 1980 to 2013 and millions of control firms. Employment shrinks 13% over two years after buyouts of publicly listed firms - on average, and relative to control firms - but expands 13% after buyouts of privately held firms. Post-buyout productivity gains at target firms are large on average and much larger yet for deals executed amidst tight credit conditions. A post-buyout tightening of credit conditions or slowing of GDP growth curtails employment growth and intra-firm job reallocation at target firms. We also show that buyout effects differ across the private equity groups that sponsor buyouts, and these differences persist over time at the group level. Rapid upscaling in deal flow at the group level brings lower employment growth at target firms.
urn:nbn:de:gbv:3:2-869142
Keywords: D24; G24; G32; G34; J23; J63; L25; 330; administrative data; business cycle; credit conditions; employment; private equity; productivity